EVALUASI LAYANAN MOOC APLIKASI PINTAR MENGGUNAKAN FRAMEWORK ITIL V4 PADA PUSDIKLAT TEKNIS KEMENAG RI - Yevi Grata Putra; Tata Sutabri (Jurnal Komunikasi, 2024)
The Technical Education and Training Center (Pusdiklat) of the Research and Development and Training Agency of the Ministry of Religion of the Republic of Indonesia plays a crucial role in increasing the capacity of human resources within the Ministry of Religion (Kemenag). The Technical Education and Training Center organizes technical training for Ministry of Religion ASN to improve their competence and professionalism. In the digital era, the use of information technology has become essential in the education and training process. The Indonesian Ministry of Religion's Technical Education and Training Center has adopted Massive Open Online Courses (MOOC) through the PINTAR application to improve the quality and accessibility of education for employees and the wider community. MOOCs, which first appeared in 2008, offer a flexible online learning model and are open to the public. The PINTAR application provides various learning materials in the form of articles, videos and assignments to improve the skills of ASN Kemenag. This research aims to evaluate the PINTAR application service using the ITIL V4 framework at the Indonesian Ministry of Religion's Technical Education and Training Center. The research methodology includes observation, interviews, and distributing questionnaires to collect data from users. The evaluation results show that the implementation of ITIL V4 improves service quality, user satisfaction and operational efficiency of the PINTAR application. However, there are several areas that need improvement, such as governance transparency, regular evaluations, and strengthening human and technical resources. This research provides recommendations for improving PINTAR application services through increasing transparency, strengthening the evaluation process, developing resource capacity, and integrating with other standards and best practices